If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 8x + -20 Reorder the terms: 0 = -20 + 8x Solving 0 = -20 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 0 + -8x = -20 + 8x + -8x Remove the zero: -8x = -20 + 8x + -8x Combine like terms: 8x + -8x = 0 -8x = -20 + 0 -8x = -20 Divide each side by '-8'. x = 2.5 Simplifying x = 2.5
| (5-3z)(5+3z)= | | 6y=7x-18 | | 90+0=180 | | 6z+1.25=7z+0.75 | | 9y=0-25 | | 5j+11=61 | | 3x+21=10x-10 | | 3x-19=4x-19 | | x=2/12=5/x-2 | | 5j+7=72 | | 2/3 | | 90-2y=-4 | | 2(3x-4)=8x+4 | | 0=10x-25 | | 11x-4x+112=11x+80 | | -(7x-2)(7x-2)= | | 2u+12=16 | | d/dx=2cos3x | | 0.15-0.03(x+1)=-0.03(2-x) | | 284.18/20.99x93 | | 2x^2=15x-7 | | r+5.2=-0.3 | | (6x+-2y)-(2x+3y)= | | 3y=0+9 | | 9w+3=57 | | .07x+.23(60)=.15(60+x) | | 18x^8-7x^6+9x^5=0 | | 5k+12=22 | | 63y+10=5y-2 | | (6x+-2y)+(2x+3y)= | | 6x+7x-21=63-8x | | 0.39a=14.4 |